O lazer traduzido nas festas e folguedos presentes na Revista Brasileira de Folclore (1961 - 1976): uma questão de educação das sensibilidades? - Jenifer Lourenco Borges Vieira (2013)
This dissertation aims to analyze the articles of the Revista Brasileira de Folclore (RBF) that specifically or indirectly, make reference to folklore that can be construed as leisure possibilities. To achieve this goal, two specific objectives were established. The first was to identify which were present in the folklore magazine that could be construed as leisure possibilities. And the second was to ascertain what was the goal of the Campanha de Defesa do Folclore Brasileiro (CDFB) to edit the RBF. Being a journal of the RBF national character, under the Ministry of Education (MEC), one can identify the proposal or bid, educational sensibilities of his readers, thinking of these sensitivities as something that refers to politics, and culture education. The time frame chosen for the study is from 1961 to 1976, due to the life cycle of the RBF have this range.